If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + -3x = x + 3x Combine like terms: x + 3x = 4x 7 + -3x = 4x Solving 7 + -3x = 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 7 + -3x + -4x = 4x + -4x Combine like terms: -3x + -4x = -7x 7 + -7x = 4x + -4x Combine like terms: 4x + -4x = 0 7 + -7x = 0 Add '-7' to each side of the equation. 7 + -7 + -7x = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -7x = 0 + -7 -7x = 0 + -7 Combine like terms: 0 + -7 = -7 -7x = -7 Divide each side by '-7'. x = 1 Simplifying x = 1
| X^2+11X+19=X-6 | | 7r+2=(5r-4) | | 8(3-5m)= | | 2(3x+3)+6(x-4)= | | 8x+17=-5(3-8x) | | 8.1-1.5x=-6.9 | | 3x^3+x^2-2=0 | | 2*5+x= | | -4(5y-6)-y=-3(y-4) | | 42y+4=16 | | 42y+4=17 | | 6.2m+3-1.9=-5.72 | | 8y=y+6+3 | | -(-(-k))-(-2)(-2+k)=-k-(4k+3) | | -2(6y-5)-y=-4(y-3) | | 15x+3=28+10x | | (5v+7)(5-v)=0 | | 8x+9=6x*15 | | -18-x=12 | | 0.63m=-3 | | -4(6y-8)-y=-4(y-3) | | -[3x+(3x+9)]=9-(4x+3) | | X-2+x-3+123=180 | | 2y+12=21 | | 44=-4v | | 3(x+1)+4=22 | | .4(x+.7)=.6x-4.2 | | 9-6y^2= | | 8+4p=10p-4 | | 10-4x=-32 | | 9k+4=22 | | 6-(b+2)= |